International Technical Digest on Electron Devices
DOI: 10.1109/iedm.1990.237214
|View full text |Cite
|
Sign up to set email alerts
|

A reliable bi-polarity write/erase technology in flash EEPROMs

Abstract: This paper describes t h e key technology t o scale down the Flash EZPROM cell, which has a conventional s e l f -a l i g n e d d o u b l e poly-Si s t a c k e d s t r u c t u r e .I t is c l a r i f i e d experimentally t h a t Flash memory c e l l w r i t t e n and erased by Fowler-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(11 citation statements)
references
References 2 publications
0
11
0
Order By: Relevance
“…From (5), we can obtain (8) If we consider (9) from (4) we can obtain an distribution equation as (10) It is manifest from Fig. 9…”
Section: Appendixmentioning
confidence: 96%
See 1 more Smart Citation
“…From (5), we can obtain (8) If we consider (9) from (4) we can obtain an distribution equation as (10) It is manifest from Fig. 9…”
Section: Appendixmentioning
confidence: 96%
“…In the past, most studies have been focused on the stress-induced leakage current (SILC) phenomenon to describe the data retention characteristics as a trap-assisted tun- neling (TAT) [9]- [13]. However, as the dimensions of the flash cells are scaled down, we have found that an annihilation phenomenon of interface states ( , : hydrogen, etc.)…”
Section: Introductionmentioning
confidence: 99%
“…By adapting channel FN tunneling write [9], the cell is able to retain data for more than ten years at 125 • C without any significant read current shift.…”
Section: Introductionmentioning
confidence: 99%
“…6,7 These stress-induced leakage currents increase with decreasing oxide thickness, 1 and set therefore a lower limit for a further reduction of the gate oxide thickness in FLASH memory based devices. 8 There is general agreement that trap-assisted tunneling is caused by the generation of traps inside the oxide during high-voltage stressing and lead to the observed stressinduced leakage currents.…”
Section: Introductionmentioning
confidence: 99%